1R Pseudo-rigid-body Model of Initially Curved Flexible Beam with End Loaded Moment - Li Yuan; Du Qiuyue (Jixie chuandong, 2018)
The initially curved flexible beam is considered as a straight beam with the free end loaded a moment Mi,and the theoretical trajectory and corner of the initially curved flexible beam’s end are derived according to the Bernoulli-Euler equation. The theoretical results are given with example,and are compared with ANSYS simulation to verify the effectiveness of the theory. Secondly,based on the1 R pseudo-rigid-body model（ PRBM） of the straight beam subjected to the moment,the 1 R PRBM of the initially curved flexible beam subjected to the moment is firstly developed and is compared with the theoretical results to verify its effectiveness. Finally,aiming at the deficiency of the PRBM model,the modified model of the 1 R PRBM of initial curved flexible beam subjected to moment is put forward and compared with the theoretical results and the 1 R PRBM model to verify its effectiveness,which lays the foundation for studying the compliant mechanism with the initially curved flexible beam.